$\displaystyle \frac{x-4}{6x-24}$÷$\displaystyle \frac{1}{4-x}$ = ? Result: $\displaystyle \frac{(x-4)(4-x)}{6x-24}$ I do not know if I should simplify this...
Follow Math Help Forum on Facebook and Google+
Originally Posted by vaironxxrd $\displaystyle \frac{x-4}{6x-24}$÷$\displaystyle \frac{1}{4-x}$ = ? Result: $\displaystyle \frac{(x-4)(4-x)}{6x-24}$ I do not know if I should simplify this... Yes you should... $\displaystyle \displaystyle \begin{align*} \frac{(x - 4)(4 - x)}{6x - 24} &= \frac{(x - 4)(4 - x)}{6(x - 4)} \\ &= \frac{4 - x}{6} \end{align*}$
Oops. I was a little too late. Lol.
Last edited by highvoltage; Mar 20th 2012 at 07:54 PM.
One "technical point": $\displaystyle \frac{(x- 4)(4- x)}{6(x- 4)}= \frac{4- x}{6}= -\frac{x- 4}{6}$ for $\displaystyle x\ne 4$. It is not defined for x= 4.
Last edited by HallsofIvy; Mar 21st 2012 at 05:04 PM.
View Tag Cloud